A prospective study of injuries to elite Australian rugby union players. Issue 4 (1st August 2002) - Bathgate, A; Best, J P; Craig, G; Jamieson, M
Abstract : Objectives: To assess injury patterns and incidence in the Australian Wallabies rugby union players from 1994 to 2000. To compare these patterns and rates with those seen at other levels of play, and to see how they have changed since the beginning of the professional era. Methods: Prospective data were recorded from 1994 to 2000. All injuries to Australian Wallabies rugby union players were recorded by the team doctor. An injury was defined as one that forced a player to either leave the field or miss a subsequent game. Results: A total of 143 injuries were recorded from 91 matches. The overall injury rate was 69/1000 player hours of game play. The injury rates in the periods before (1994–1995) and after (1996–2000) the start of the professional era were 47/1000 player hours and 74/1000 player hours respectively. The lock was the most injured forward, and the number 10 the most injured back. Most injuries were soft tissue, closed injuries (55%), with the head being the most commonly injured region (25.1%). The phase of play responsible for most injuries was the tackle (58.7%). Injuries were more likely to occur in the second half of the game, specifically the third quarter (40%). The vast majority of injuries were acute (90%), with the remainder being either chronic or recurrent. Conclusions: Injury rate increases at higher levels of play in rugby union. Injury rates have increased in the professional era. Most injuries are now seen in the third quarter of the game, a finding that may reflect new substitution laws. There is a need for standardised collection of injury data in rugby union.